Computational Intelligence Techniques and Phylogenetic Trees for Identification of Sedimentary Petrofacies - Saporetti, Camila M.; Goliatt, Leonardo; de Oliveira, Leonardo C.; Pereira, Egberto (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2018)
The heterogeneities are characterized by several sedimentary petro- facies. Petrofacies identification involves manual processes and time-consuming analyses. The study of the diagenesis has been encouraged by petroleum companies, in order to understand the distribution of porosity in sandstones. This work aims to analyze the use of clustering approaches to identify petrofacies and assist the analysis of petrographic data. In addition, this study introduced the use the phylogenetic analysis tools to understand the diagenetic process that occurred during sedimentary rock formation. The proposed methodology reaches similar results to those obtained by the conventional method of individualization while allows for reducing time and cost in the individualization task.